Multi-omics analysis reveals the specific role of biocontrol reagents against tomato bacterial wilt - Du, Xin-Qiao; Sun, Tian-Xiao; Xu, Wu-Lin; Zhu, Tang; Wang, Qiang; Gu, Pei-Wen; Lu, Jiang (Frontiers in Plant Science, 2025)
Bacterial wilt caused by Ralstonia solanacearum is considered one of the most important diseases that cause economic losses to tomato. Currently, eco-friendly biocontrol agents have been increasingly considered as effective approaches to control tomato bacterial wilt. However, the specific mechanisms by which biocontrol bacteria with distinct functions exert their effects remain unclear. In this study, we employed a combination of amplicon sequencing, transcriptomics, and metabolomics analysis to investigate how Bacillus velezensis and Pseudomonas fluorescens affect the defense responses against R. solanacearum in tomato. We showed that the fermentation broth of these biocontrol agents inhibited the growth of R. solanacearum in vitro, and improves the ability of tomato plants against bacterial wilt. In general, different biocontrol agents protect plants from bacterial wilt in many ways, by recruiting specific microbial communities in rhizosphere soil and activating different synthetic/metabolic and signaling pathways. Collectively, our findings contribute to a more in-depth understanding in disease resistance mechanisms of biocontrol agents, and provide a theoretical foundation for the development of targeted strategies using beneficial microorganisms to suppress disease occurrence.